Paradoks antara Nilai Pengabdian dan Profesionalisme dalam Manajemen Kinerja Tenaga Pengajar Pesantren Modern - Adib Aqil Haidar (CV. Laskar Karya, 2025)
This study investigates the paradox between spiritual devotion (khidmah) and professional work ethics within the performance management system of educators at Pondok Pesantren Nurul Fatta. The modernization of Islamic educational governance has shifted the meaning of khidmah from a form of sincere spiritual service toward a professional responsibility emphasizing accountability and measurable performance. The study aims to analyze the transformation of khidmah’s meaning, identify tensions between spiritual and professional motivations among educators, and formulate an integrative performance management model that harmonizes spiritual values with professional standards. A qualitative approach with a case study design was employed. Research subjects included pesantren leaders, educators, and administrative managers. Data were collected through observation, in-depth interviews, and document analysis, and then analyzed using Miles and Huberman’s interactive model consisting of data reduction, data display, and conclusion drawing. The findings reveal a shift in the meaning of khidmah from spiritual to professional orientation, the emergence of value tension in work motivation, and the need for a management system capable of integrating both orientations. The novelty of this research lies in the development of a Faith-Integrated Performance Appraisal Model, which adapts the principles of Psychological Contract Theory and Dual Motivation Theory to the context of Islamic educational institutions. This study contributes to strengthening value-based performance governance that not only emphasizes organizational efficiency but also preserves the essence of spirituality within educational management practices.